New perspectives on molecular simulation of chemistry and physics in external electric fields. Issue 47 (17th November 2022) - Kusalik, Peter G.; Gracheva, Maria E.; Shaik, Sason; English, Niall J.
Abstract : This themed collection includes a collection of articles on molecular simulation of chemistry and physics in external electric fields.